The Urgency of Revision of the Rubber Article in the ITE Law No. 19 of 2016 - widaningsih widaningsih (Journal of Social Science and Humanities, 2025)
The development of information and communication technology has changed the behavior and lifestyle patterns of society as a whole, transcending the world and bringing changes in various fields. Information technology not only contributes to human well-being, progress and advancement of civilization, but can also be an effective means of breaking the law. The purpose of the enactment of the ITE Law is also to ensure the recognition and respect for the rights and freedoms of others in accordance with existing legal corridors. Unfortunately, the ITE Law has several articles that cause multiple interpretations in society, or better known as the rubber article. The purpose of this study is to reveal the urgency of the revision of UU ITE no. 19 of 2016. The method used in this research is normative and legal, using the technique of collecting library research materials. In summary, amendments to the ITE Law are very much needed to prevent incidents involving multiple interpretation articles. The provisions of the ITE Law which can be interpreted many times have negative impacts such as limited freedom of opinion in expressing opinions and criticism, lack of legal certainty in supporting the law, and the possibility of being misused and also the possibility of excessive crimes.